The effective methods for analyzing and interpreting data in classroom action research - Rahmadani (Balai Diklat Keagamaan Ambon, 2024)
Educators widely use Classroom Action Research (C.A.R.) to improve teaching quality. In its process, effectively analyzing and interpreting data becomes crucial to generating valid and relevant findings. However, many teachers still need help with analyzing and interpreting C.A.R. data. This article discusses practical ways to analyze and interpret C.A.R. data so teachers can better understand it. The method used in this research is qualitative with descriptive analysis. The results from the literature review and examination of C.A.R. reports show several C.A.R. data collection techniques, including interviews, observations, questionnaires, and documentation. Meanwhile, interviews with teachers who have conducted C.A.R. revealed that C.A.R. data analysis techniques are divided into two types: quantitative data analysis and qualitative data analysis. Every piece of data analyzed requires interpretation to understand the obtained data properly. Applying appropriate strategies in managing C.A.R. data can lead to more accurate and applicable interpretations. This can support more effective decision-making as part of efforts to improve learning. The implication of this study is the development of a practical guide, complete with examples, for conducting C.A.R. data analysis and interpretation, which teachers and other education practitioners can use.